Impact of prenatal nutritional interventions on low birth weight in low- and middleincome countries: A systematic review - Houssou, Gbèmahon-Roger; AZANDJEME, COLETTE SYLVIE; FANOU, NADIA; Gbaguidi, Schadrac; METONNOU, CLÉMENCE GERMAINE (My University, 2023)
Introduction: Undernutrition during pregnancy is an indicator of intrauterine growth restriction, a critical factor in low birth weight. This review aimed to summarize evidence of nutritional interventions targeting pregnant women to reduce low birth weight in low- and middle-income countries (LMICs). Method: A total of 15 systematic reviews were included for the narrative synthesis after an exhaustive literature search on the search engines Pubmed, google scholar, and the Cochrane database. Systematic reviews of randomized controlled trials evaluating the effect of nutritional interventions during pregnancy on the risk of low birth weight were included. The methodological quality of the included studies was assessed using the AMSTAR assessment tool by two authors. Results: The interventions identified were nutrition education, protein supplementation, lipid supplementation, and multiple or single micronutrients such as vitamin D, iron, zinc, calcium, folic acid, and iodine. Except for vitamin A, iodine, and calcium supplementation, all interventions were useful and could be considered to reduce low birth weight. The effect of zinc supplementation needed to be clarified. Conclusion: Except for vitamin A, iodine, and calcium, all interventions could impact the child's birth weight. Nutritional education interventions should be combined with other strategies, such as supplementation.
Keywords: Impact; Nutritional intervention; Low birth weight; Pregnant women